The Effect of the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH) on the Human Development Index (HDI) in Surabaya City - Muhammad Maulana; Joko Priyono (Journal of Macroeconomics and Social Development, 2026)
This study aims to analyze the effect of the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and the Revenue Sharing Fund (DBH) on the Human Development Index (HDI) in Surabaya City during the period 2010–2024. A quantitative approach was employed using a multiple linear regression method based on secondary time-series data obtained from official government institutions. The results indicate that DAU, DAK, and DBH simultaneously have a significant effect on the Human Development Index. Partially, the Special Allocation Fund exhibits the strongest and most significant influence, reflecting its targeted allocation toward basic public service sectors, particularly education and health. The General Allocation Fund also has a positive and significant effect by strengthening overall regional fiscal capacity to support public service provision. In contrast, the Revenue Sharing Fund shows a positive but statistically insignificant effect on the Human Development Index. These findings suggest that improving human development outcomes in Surabaya City requires more targeted, effective, and equitable management of intergovernmental transfer funds, with a stronger emphasis on enhancing the quality of basic public services.